2006
DOI: 10.1158/1535-7163.mct-06-0424
|View full text |Cite
|
Sign up to set email alerts
|

Association of insulin-like growth factor binding protein-3 expression with melanoma progression

Abstract: Previous studies from our laboratory have identified several endothelial cell -associated marker genes implicated in human melanoma metastasis via tumor vasculogenic mimicry. In this study, we used dual model systems composed of melanoma cell lines and clinical melanoma samples to validate the importance of insulin-like growth factor binding protein-3 (IGFBP-3) as a marker involved in disease progression. Gene expression analysis was done using a microarray approach for both primary and metastatic melanoma sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 26 publications
4
41
2
1
Order By: Relevance
“…Similar to our findings, which showed that IGFBP-3 is involved in malignant glioma cell motility and migration, an earlier report has shown that IGFBP-3 is essential for the migration of melanoma cells. 59 On the contrary, some studies have shown IGFBP-3 significantly reduces the migration of PC3 prostate cancer cells, Ewing's sarcoma cells, and non-small cell lung cancers, further emphasizing the multifunctional roles of IGFBP-3 in different human cancers. 4,35,38 Our results demonstrating IGFBP-3's involvement in GBM tumor cell invasion in vitro are also consistent with the findings of previous studies on malignant melanoma and esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, which showed that IGFBP-3 is involved in malignant glioma cell motility and migration, an earlier report has shown that IGFBP-3 is essential for the migration of melanoma cells. 59 On the contrary, some studies have shown IGFBP-3 significantly reduces the migration of PC3 prostate cancer cells, Ewing's sarcoma cells, and non-small cell lung cancers, further emphasizing the multifunctional roles of IGFBP-3 in different human cancers. 4,35,38 Our results demonstrating IGFBP-3's involvement in GBM tumor cell invasion in vitro are also consistent with the findings of previous studies on malignant melanoma and esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, besides miR-15a and miR-16-1, other miRNAs such as miR-183, miR-190, miR-24-1 and miR-213 are known to have reduced expression in B-CLL [25]. Other than B-CLL, changes in miRNA expression have also been documented for other cancers [22,26]; hence, miR-143 and miR-145 are significantly reduced in colorectal cancers [27]. Taken together, extant findings are consistent with a general role played by various miRNAs in many neoplasms.…”
Section: Reduced Mirna Expression Correlates With Cellular Transformamentioning
confidence: 99%
“…There are reports of IGFBP-3 overexpression in squamous cell lung cancer (26), localized prostate cancer (27), pancreatic adenocarcinoma (28), clear cell renal cell carcinoma (29), metastatic melanoma (30), and breast cancers with poor prognosis (31). In contrast, in patients with HCC, IGFBP-3 mRNA is consistently expressed at a lower level in tumor tissue than in healthy liver (3,16).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas inhibitory effects have been observed in endometrioid ovarian cancer (42), Ewing's sarcoma (43), and non-small cell lung cancer cells (44), IGFBP-3 can induce migration in melanoma (30) and breast cancer (38) cells, as well as umbilical vein (45) and retinal (46) endothelial cells. Furthermore, increased IGFBP-3 expression has been observed in liver and lymph node metastases of pancreatic endocrine neoplasms (47), although it is antimetastatic in lung cancer (44).…”
Section: Discussionmentioning
confidence: 99%